From Venture Idea to Venture Opportunity - Vogel, Peter (Entrepreneurship Theory and Practice, 2017)
Opportunities are a core construct in the field of entrepreneurship. Despite recent advances suggesting the separation of ideas from opportunities, the field still suffers from conceptual deficiencies. This article builds on this distinction and leverages insights from creativity and innovation management literature to propose a framework that allows tracing the evolution of a venture from first insight to exploitation. It discusses real–time/longitudinal and retrospective measurement techniques from the fields of entrepreneurship, creativity, and innovation management to empirically capture the framework. Several research questions for future studies are provided, concluding with a discussion of implications for research and practice.